Preparation of mixed matrix composite membrane for hydrogen purification by incorporating ZIF-8 nanoparticles modified with tannic acid. (4th March 2020) - Chen, Feng; Dong, Songlin; Wang, Zhi; Xu, Jiayou; Xu, Rui; Wang, Jixiao
Abstract: The incompatibility between nanofillers and polymer, caused by the agglomeration of nanoparticles and their weak interaction with each other, is still a challenge to develop mixed matrix composite membrane. Herein, we introduced the ZIF-8-TA nanoparticles synthesized by in situ hydrophilic modification into the hydrophilic poly(vinylamine) (PVAm) matrix to prepare composite membranes for H2 purification. The dispersion of ZIF-8 in water was improved by tannic acid modification, and the compatibility between ZIF-8 particles and PVAm matrix was enhanced by chemical crosslinking between the quinone groups in oxidized tannic acid (TA) and the amino groups in PVAm. Moreover, the compatibility between hydrophobic polydimethylsiloxane (PDMS) gutter layer and hydrophilic separation layer was achieved by the adhesion of TA-Fe 3+ complex to the surface of PDMS layer during membrane preparation. The interlayer hydrophilic modification and the formation of separation layer were accomplished in one step, which simplified the preparation process. The experimental results indicated that when the TA addition used for modification was 0.5 g and the ZIF-8-TA0.5 content in membrane was 12 wt%, the prepared membrane showed the best separation performance with the CO2 permeance of 987 GPU and the CO2 /H2 selectivity of 31, under the feed gas pressure of 0.12 MPa. Highlights: ZIF-8-TA nanoparticles were synthesized by in situ hydrophilic modification. ZIF-8-TA showed good compatibility with PVAm. TA-Fe 3+ complex improved the compatibility between separation layer and PDMS layer. The one-step prepared mixed matrix composite membrane showed excellent CO2 /H2 separation performance.